Constructive method for solving a nonlinear singularly perturbed system of differential equations in critical case. (1993) - Slavova Slavova, Angela Angela
Abstract : A singularly, perturbed system of differential equations with degenerate matrix at the derivative is considered. The existence and construction of the periodic solutions are investigated in critical case. For the analysis of these algorithms the apparatus of Lyapunov's finite majorizing equations is used. An implementation of this method is given in two examples.